دور الـ Daphnia magna في المكافحة الحيوية للطفيلي الهدبي Ichthyophthirius multifiliis عند أسماك الكارب العادي(Cyprinus carpio L.) - ديوب أمل; سابا ميشيل; قتابي رشا (Latakia University Journal -Biological Sciences Series, 2017)
أجريت الدراسة بهدف تقييم فعالية الـ Daphnia magna (من متفرعات القرون Cladocera) في استهلاك الشكل الإعاشي لوحيد الخلية الهدبي Ichthyophthirius multifiliis, الذي يخمج سطح جسم أسماك الكارب العادي وغلاصمها. جمعت الأسماك والـ D.magnaبشكل متزامن، وعشوائياً، من أحواض الأسماك في مزرعة السن, وتم أقلمة الـ D.magna واستزراعها مخبرياً. بينت نتائج الدراسة, باستخدام العدسة المكبرة, شراهة الـD.magna على استهلاك الأشكال الإعاشية للطفيلي الملونة بصبغة غيمزا Giemsa (مخبرياً), حيث أدخلت أجزاء الطفيليات, بعد تخريبها, عبر حجرة ترشيح الـ D.magna ووصلت إلى الأمعاء. بلغت نسبة استهلاك الطفيلي من قبل الـ D.magna 65% بعد نصف ساعة, و 100% بعد ساعة. تفيد هذه النتيجة في استخدام الـ D.magna في المكافحة الحيوية للطفيلي المذكور, وتعد مثل هذه الدراسات في هذا المجال حديثة العهد في العالم وهي تنفذ لأول مرة في سورية. Study was performed to evaluate the effectiveness of Daphnia magna (Zooplankton: Cladocera) to consume of parasitic ciliate Ichthyophthirius multifiliis, which infect surface body and gills of common carp fish. Fish and Daphnia samples were collected from fish ponds in Al-sinn fish farm, simultaneously and randomly, then D.magna were adapted and cultured in the lab. Results showed efficiency of D.magna to consume vegetative form of Ich.multifiliis by using Giemsa dye and magnifying glass, whereas parts of parasite were entered through filtration chamber of Daphnia after its destruction, then rested in intestine. The percentage of consumption this ciliate parasite, was 65% after half an hour, and 100% after an hour. This result shows the importance of D.magna in biological control of Ich.multifiliis parasite. These studies in this field are new in the world, our study is done for the first time in Syria.